Modern furniture and fittings : the design and construction of modern furniture for houses and public buildings, domestic furniture, library and study furniture, furniture components, church furniture and fittings, plywood and lamin board technique, framed and flush panelling, shop and exhibition cases - 402077 Hooper, John; Hooper, Rodney (London : Batsford, 1955)
22